Climate change and human mobility : global challenges to the social sciences - Hastrup, Kirsten; Olwig, Karen Fog, 1948- (Cambridge University Press, 2012)
"'The greatest single impact of climate change could be on human migration', stated the Intergovernmental Panel on Climate Change (IPCC) in 1990. Since then there has been considerable concern about the large-scale population movements that might take place because of climate change. This book examines emerging patterns of human mobility in relation to climate change, drawing on a multidisciplinary approach, including anthropology and geography. It addresses both larger, general questions and concrete local cases, where the link between climate change and human mobility is manifest and demands attention - empirically, analytically and conceptually. Among the cases explored are both historical and contemporary instances of migration in response to climate change, and together they illustrate the necessity of analyzing new patterns of movement, historic cultural images and regulation practices in the wake of new global processes"--